Machinery Regulation and Remanufacturing: A Link Between Machinery Safety and Sustainability - Stefano Beneduce; Leonardo Vita; Luciano Cantone; Francesco Caputo (Machines)
On 14 June 2023, the European Parliament adopted Regulation (EU) 2023/1230 on machinery, which entered into force on 19 July 2023 (with some exceptions as per art. 54, according to a corrigendum issued to address a clerical error as regards the application dates in the original version) and shall apply from 20 January 2027, replacing the Machinery Directive 2006/42/EC. The main innovations/differences introduced by the Machinery Regulation (MR) compared to the Machinery Directive (MD) are critically analysed here, with a focus on sustainability issues. Some of these issues are covered by several international standards (such as BS 8887, ISO 10987 or DIN 91472), which also define the criteria and requirements for the remanufacturing process, although some technical gaps remain. Using the example of agricultural machinery, this paper proposes a methodology for determining the areas of acceptability for remanufactured products: these are expressed in terms of structural performance (e.g., the number of cycles ahead to failure expressed as the mutual of damage <semantics>1−D=0.625</semantics>) and the functional and safety requirements of the original machine. In this way, the issue of “substantial modification of machinery” is explored in terms of the safety obligations that the remanufactured machinery must fulfil. The paper is therefore a contribution to circular design by providing general criteria for the extension of the service life of machinery while at the same time considering safety issues.